オホーツク海天然ガスハイドレートの同位体組成とその結晶特性 - 八久保, 晶弘; 坂上, 寛敏; 南, 尚嗣; 布, 川 裕; 庄, 子 仁 (Chigaku Zasshi (Jounal of Geography), 2009)
New hydrate-bearing seepage structures off Sakhalin in the Sea of Okhotsk were investigated from 2003 to 2006 within the framework of the CHAOS project. We obtained samples of natural gas hydrate and measured the molecular and isotopic compositions of hydrate-bound gas. Methane δ13C and δD were in the range of －67 to －63‰ and －207 to －193‰, respectively. These results indicate a microbial origin produced by CO2 reduction according to Whiticar's diagram. Because ethane δ13C showed a thermogenic origin, hydrate-bound gas contains a small amount of thermogenic gas. The hydration numbers of the samples were estimated as 6.19 ± 0.02 using the Raman spectra of the C?H stretching mode and a thermodynamic calculation. Heat flow calorimetry revealed that the values for dissociation heat of the samples were 18.1 ± 0.3 kJ mol－1（ from hydrate phase to gas and ice phases） and 55.4±0.4 kJ mol－1（ from hydrate phase to gas and water phases）, which agree well with the values in of literature. journal article